Processo de formação de estratégias: um estudo numa Instituição federal de ensino do estado do rio grande do norte - Oliveira, Rinaldo Medeiros Alves de (Universidade Federal Rural do Semi-Árido, 2018)
of education, science and technology of Rio Grande do Norte state, from 1910 to 2018. To this end, it was sought to identify the significant events, the phases and the strategic changes throughout the organizational path; to analyze the main organizational implemented strategies and their training processes; and to investigate how the environment influences the process of strategy formation. To promote the achievement of the goals, it was developed a case study of qualitative nature, by building a theoretical basis according to the concepts relating to processes of strategy formation, compared to the findings collected by study, grounded in bibliographic and documental surveys, as well as semi-structured interviews applied to seven members from the institution managers. The data analysis includes all perspectives about the studied phenomenon, identifying, in addition to the significant events, six stages and four strategic changes that guided the path of organization. It was identified the processes of strategy formation occurred predominantly by the planning mode, admitting in a discreet way inserts of actions based on adaptive and entrepreneur modes; and in their general mass by deliberate strategies. Outcome analyses showed that the strategies of the organization are based by influence of governments and the commitment of their leaders. Finally, it can be noted that since the formation of the Council of representatives until the adoption of the Senior Board, those collegiate influence significantly the strategy development
Keywords: Processo de formação de estratégias; Mudança estratégica; Instituto Federal; Process of strategy formation; Strategic change; Federal Institute; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES